(untitled) (Fiep Bulletin - online, 2014)
Asymmetries in muscle strength exceeding 15% between the two lower-limbs are considered potential causative factors of injury. The objective of the study was to determine the percentages of strength asymmetry between the lower-limbs of school children and investigate whether values >15% correlated with performance in speed drills. The sample was composed of N=138 students (72 M and 66 F, 12.0±1.1 yrs; 52.4±11.1 Kg, 159±0.08 cm) attending the first 3 years of an Italian middle school. Lower-limb strength asymmetries were assessed using the tests: One-Leg Hop (OLH ), One-Leg Triple Hop (OLTH ) and Side Hop (SH ); running speed was assessed using the tests: 10 and 20m sprint, 10x5m Shuttle Sprint and 4.115m Side Steps and Forward (4.115m SSF ). To test for correlations between lower-limb asymmetries and running speed performance, Pearson’s correlations were calculated. Statistical significance was considered for p<0.05. Performances in the OLTH test revealed that an astonishing 65% of male school children present levels of asymmetry >15%. Pearson’s correlations revealed that values of asymmetry >15% in the OLH and OLTH tests positively correlate with performance in the shuttle test (r=0.452, N=23; p<0.05) and 4.115m SSF test (performed on the right leg; r=0.706, N=25; p<0.01). Thus, running drills requiring lateral movements and changes in direction are affected by imbalances in lower-limb muscle strength in children and adolescents. Compensation strategies aimed at diminishing the percentage of strength asymmetry should be introduced into physical education lessons within schools in order to reduce the risk for injury.